Changes in the profile of inequality across Europe since 2005: austerity and redistribution - Markus P.A. Schneider; Stephen Kinsella; Antoine Godin (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
We present two Gini-like inequality indices that provide a more nuanced picture of how the profile of inequality has changed across European countries since 2005. We use these indices to analyse the distributional changes that can be attributed to the push for austerity. We estimate the JV-indices for 24 European countries over 9 years, and then use this panel to analyse the distributional effects of the fiscal consolidation policies Europe endured after the 2008 crisis. We find that austerity increased income inequality in eurozone countries, but reduced income inequality in countries that do not use the euro as their currency. We uncover a significant new relationship between austerity policies and the tails of the income distribution, further suggesting that in the eurozone these policies on average amount to a redistribution from the bottom to the top.
Keywords: D31; D63; E62; E65; H6; 330; austerity; Europe; inequality; income distribution; Gini; Lorenz curve